Fluorescence enables high throughput screening of polyelectrolyte–protein binding affinities. Issue 43 (20th October 2022) - Mustafa, Ahmed Z.; Kent, Ben; Chapman, Robert; Stenzel, Martina H.
Abstract : Förster resonance energy transfer (FRET) in combination with high throughput controlled radical polymerisation allows quick identification of polymers that can bind strongly to enzymes such as glucose oxidase. Abstract : The use of polyelectrolytes to stabilise and deliver polymers relies on a detailed understanding of their binding, but this can be hard to measure across large numbers of samples and at low concentration. In this work, we report the use of Förster resonance energy transfer (FRET) in combination with high throughput controlled radical polymerisation to read out structure–property relationships in polyelectrolyte/protein binding. A range of different Cy5 labelled polymeric structures were prepared at 100 μL scale without prior deoxygenation and self-assembled with a model protein, glucose oxidase GOx. The resulting FRET was found to correlate with the binding strength, and not the raw number of polymers loosely bound, as measured by small angle X-ray scattering (SAXS) and isothermal calorimetry (ITC). Both our synthetic methodology and read out methods are amenable to high throughput processing, providing a platform for the rapid combinatorial design of complex polyelectrolytes.